Lost Victories - Manstein, Erich von 1887-1973; Edited and Translated by Powell, Anthony (London Methuen and CO. LTD., 1958)
Memoirs of campaigns in Poland, France and Russia.
Include Appendix and Index
Keywords: World War (1939-1945) -- Military campaigns -- Germany